47 A wide range of catheter ablations can be safely performed without interrupting novel oral anticoagulants. (5th June 2017) - Velu, Selvakumar; Pathiraja, Janaka; Lapper, Andrew; Kidd, Geoff; Arya, Anita; Barr, Craig; Forsey, Peter; Petkar, Sanjiv
Abstract : Introduction: Catheter ablation, in the immediate peri-and post procedural period is associated with a transiently increased thrombogenic state secondary to atrial inflammation arising as a result of endothelial damage caused by manipulation of ablation catheters and/or ablation lesions. For atrial fibrillation(AF) ablations, the 2016 European Society of cardiology Guidelines recommend uninterrupted warfarin therapy in the peri-procedural period. In observational cohorts and one randomised study (PIONEER-AF), uninterrupted NOAC therapy has also been found to be safe in patients undergoing AF ablations. EHRA states that simple ablation procedures have a low bleeding risk while complex ablation procedures have high bleeding risk. We describe our experience of a wide variety of catheter ablations performed on uninterrupted NOAC therapy and compare our results with similar procedures undertaken on uninterrupted warfarin therapy. Methods: A retrospective analysis of the NICOR database for all ablations undertaken on uninterrupted anticoagulation at the New Cross Hospital, Wolverhampton, between April 2014 and August 2016 was undertaken. Data regarding the number and type of procedures, type of oral anticoagulation (warfarin versus NOACs), frequency of trans-septal punctures, DCCV during procedures and complications were analysed. Results: Atrial of 648 ablations were performed in the study period of which328(50.7%) were undertaken on uninterrupted anticoagulants (uninterrupted warfarin group (uW Grp): 228 (35.1%) and uninterrupted NOAC group (UNOAC Grp): 101 (15.5%). Mean age was 59 in both groups with more male preponderance in the NOAC group. A range of simple and complex ablations were done including 131 (57.4%) AF in UW Grp compared to 26 (26.5%) in the uNOAC grp. Trans-septal punctures were more common in the UW Grp compared to the uNOAC Grp, however cardioversions (both external and internal) were used in similar fashion. Composite of bleeding and thrombo-embolic complications were relatively low in both the groups [n=5(2.1%) in the VKA group compared to n=1 (0.9%) in the UNOAC Grp with OR 2.21 (95% CI 0.25 to 19.2; p=0.47)]. Conclusions: Our experience suggests that a wide range of simple and complex ablation procedures can be safely performed ion uninterrupted NOAC therapy. Complications in the uNOAC Grp were lower than the uW Grp, reflecting growing confidence among electrophysiologists to undertake such procedures even in the absence of antidote for majority of the NOACs.